Essential Elements of Principal Leadership: A Literature Review of the Leadership Qualities of Primary and Secondary Principals - Chen, Xuan; Chen, Hong (Science Insights Education Frontiers, 2024)
Amidst ongoing educational reform around the world, the leadership qualities of primary and secondary principals have captured the increased interest of researchers. This article aims to explore the essential components of principal leadership by conducting a literature review of relevant research both in China and other countries. The survey finds that despite the variations in the definitions of principal leadership in different regions and at different times, there are still certain shared key elements in them. It summarizes the core qualities of principal leadership at the basic education level in terms of personal traits, the capacity to influence people, and the ability to make sustainable organizational improvements.